Perbandingan Efektivitas Pemberian Silver Sulfadiazine dengan Gel Lidah Buaya (Aloe Vera) 99% pada Tikus Putih ( Rattus Norvegicus L.) Jantan Galur Wistar Sebagai Pengobatan Luka Bakar - Atika Rahmi; Ratih Yulistika Utami; Hervina Hervina; Humairah Medina Liza Lubis (UMSU, 2020)
Introduction: Burn injury is a common cause of morbidity and mortality. Outcomes of morbidity and disability for deep burns patients still not improved. Many modalities for wound bed preparation was not satisfied. Aloe vera gel have been used as an anti-inflammatory natural agent, for treatment many deseases. It has also been used in the traditional medicine of many cultures and said to be beneficial in the treatment of disorders such as burns Objective: To find out the comparison of the effectiveness of administration of silver sulfadiazine and aloe vera gel 99% as a treatment of burns in white rat (Rattus norvegicus L.) male Wistar strain. Methodology: The research used True Experiment method with